Ordering countries when managing COVID-19 - Cadena, Meitner; Méndez, Marco (Frontiers in Applied Mathematics and Statistics, 2023)
Assessment of management of the COVID-19 pandemic performed by countries is analyzed by using the measure of reliability $P(X≤ Y)$. In this management, all kind of strategies as interventions deployed by governments as well individuals' initiatives to prevent, mitigate, and reduce the contagion of this disease are taken into account. Also, typical customs practiced locally and influencing contagion are included. Regarding a number of countries and rates associated to deaths and incidence, orderings of countries about such management are established, by using the measure of reliability indicated above. In this way, countries are distinguished from each other depending on how they managed this pandemic. reliabilities. This kind of analysis may also be applied to analyze the management of other diseases.